Multilevel clinical psychological intervention after the earthquake in Norcia community: a pilot study - Sambucini, Daniela; Pellicano, Gaia Romana; Ciacchella, Chiara; Begotaraj, Edvaldo; Pierro, Laura; Cinotti, Francesca; D’Orazio, Edoardo; Lai, Carlo (Psychology Hub, 2020)
Aim of the study was to explore the psychological well-being of Norcia’s teachers and students 3 years after the earthquake, and to verify the effectiveness of the Pennebaker’s expressive writing intervention (EWI) on a group of high-school students. In the first step of the study a drawing participative action-intervention, lasting three days, was carried out with twelve teachers of primary, middle and high school and their students. From the first step, emerged fear and anxiety related to the earthquake, and that the sense of belonging to Norcia community appeared to be an integrative factor against the dissociative feelings of the trauma. Starting from these results, in the second step of the study, the EWI was carried out on a sample of 18 high-school students. The participants were instructed to write for three days about feelings related to Norcia earthquake (experimental group) and about a non-emotional account of daily activities (control group). Before (T0) and 1 month after (T1) the EWI, levels of anxiety, the depression, the trauma symptom, dissociation, post-traumatic growth were measured. Moreover, the territorial sense of community was assessed at T0. Results of the second steps showed that the writing intervention did not reduce the psychopathological symptoms of the experimental group. However, it emerged that the sense of community could be a protective factor against the depression symptoms and could have an important facilitating role for the post-traumatic growth.